The Contribution of the Smart Board to the Improvement of Learning Results in the Subject of Mathematics - Senad Orhani (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
This research aims to explore the contribution of the Smart Board in improving students' results in mathematics. The main goal of our research is to reveal and understand how the Smart Board contributes to the improvement of students' results in the subject of mathematics. With a special focus on upper secondary school students, this study uses qualitative methodology to understand the contribution of technology to the learning process and students' skills. Teachers and students were interviewed to highlight their perceptions and experiences regarding the use of the Smart Board. The results provide a clear look at the role and value of the Smart Board in mathematics classrooms, addressing potential issues and making recommendations for more successful use of this technology in education. This research contributes to the existing literature related to the use of technology in the field of education and brings a new perspective on the use of the Smart Board in the context of mathematics in the classroom. The results of this research confirm that the Smart Board has a positive impact on the mathematics learning process and student motivation. Detailed discussion of these points will provide a rich and concise summary of the findings and their implications for the field of education.